Breeding for Heat Tolerant Aromatic Rice Varieties and Identification of Novel QTL Regions Associated with Heat Tolerance During Reproductive Phase by QTL-Seq - Surangkana Chimthai; Sulaiman Cheabu; Wanchana Aesomnuk; Siriphat Ruengphayak; Siwaret Arikit; Apichart Vanavichit; Chanate Malumpong (Rice Science)
Extremely high temperatures resulting from climate change have become a major challenge for increasing rice production. Therefore, our objective was to develop heat-tolerant aromatic rice varieties using the pedigree method, focusing on selecting for seed-setting ability under extremely high temperatures along with the use of single nucleotide polymorphism/insertion and deletion (SNP/InDel) markers to improve aromatic properties and grain quality. Furthermore, the QTL-seq approach was utilized to identify QTLs for seed-setting rate in an F2 population subjected to heat stress. The candidate QTL regions were then aligned to confirm SNPs/InDels in synonymous F7 candidate heat-tolerant lines. The results revealed that four promising lines, namely 84-7-1-9, 84-7-1-10, 159-3-3-1, and 159-3-3-10, were classified as heat-tolerant with low amylose content. In addition, lines 84-7-1-9 and 84-7-1-10 were identified as aromatic rice encompassing the aroma gene (badh2). Regarding the QTL-seq results, the qSF2.1 region ranged from 311 051 to 3 929 422 bp on chromosome 2, was identified based on the highest contrasting SNP index between the heat-susceptible and tolerant bulks. The candidate genes within this region include two genes related to heat shock proteins, three genes associated with pollen fertility, and four genes involved in heat stress and other abiotic stress responses. These genes are proposed as potential candidates for heat tolerance and could serve as targets in rice breeding programs aimed at enhancing heat tolerance.